2016
DOI: 10.33225/jbse/16.15.424
|View full text |Cite
|
Sign up to set email alerts
|

Learner’s Alternative and Misconceptions in Physics: A Phenomenographic Study

Abstract: This phenomenographic case study attempted to determine the alternative and misconceptions of learners in selected concepts in Physics. The research adds another dimension to understanding alternative conception in kinematics by qualitatively determining how learners describe/define a distance of 0m, a displacement of 0m, a speed of 0m/s, a velocity of 0m/s as well as an acceleration of 0m/ss. Data were gathered by means of a free response test. Senior high school grade 12 learners were purposefully selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Even though the resultant force should be proportional to the change in the velocity of the object, not the velocity of the object. The results of this study are in line with several previous studies which showed that many students had difficulties in understanding physics in graphical representation (Klein et al, 2017;Motlhabane, 2016).…”
Section: Figure 3 Pretest-posttest Question Sample (Question Number 5)supporting
confidence: 92%
“…Even though the resultant force should be proportional to the change in the velocity of the object, not the velocity of the object. The results of this study are in line with several previous studies which showed that many students had difficulties in understanding physics in graphical representation (Klein et al, 2017;Motlhabane, 2016).…”
Section: Figure 3 Pretest-posttest Question Sample (Question Number 5)supporting
confidence: 92%
“…Graphs of position, velocity and acceleration are fundamental in teaching about motion, and many researchers have studied student difficulties, as reviewed e.g. in [5]. Even if students entering introductory physics classes understand the basic construction of graphs, they often find it difficult to apply those skills to the tasks they encounter in the physics courses [6].…”
Section: Understanding Of Graphs Of Position Velocity and Acceleratio...mentioning
confidence: 99%
“…Then, the showed that the character assessment of students in New York still uses the conventional method, where in this case the teacher has difficulty in assessing the character possessed by students [89]. Furthermore, shows that there are still many students in Africa who experience minimal character values due to the difficulty of teachers in conducting these character assessments [90].…”
Section: Introductionmentioning
confidence: 99%